2016
DOI: 10.1002/jctb.5078
|View full text |Cite
|
Sign up to set email alerts
|

Removal of sulfuric acid aerosols in desulfurized flue gas by adding moist air

Abstract: BACKGROUND: The reduction of sulfuric acid aerosol emissions in coal fired power plant is of great importance. Based on the classical theory of heterogeneous vapor condensation, a novel engineering process was proposed to increase the efficiency of removal of sulfuric acid aerosols by adding moist air in the condensational growth chamber (CGC), following the desulfurization scrubber. RESULTS:The theoretical analysis showed that this novel process was feasible. The experimental results indicated that the effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…This finding indicates that when L/G ratio increases, the mean diameter of aerosol particles enlarges. This conclusion is consistent with the simulation and experiment results of previous studies. …”
Section: Resultssupporting
confidence: 93%
“…This finding indicates that when L/G ratio increases, the mean diameter of aerosol particles enlarges. This conclusion is consistent with the simulation and experiment results of previous studies. …”
Section: Resultssupporting
confidence: 93%
“…Studies have indicated that the SO 3 synergistic removal efficiency of WFGD is mainly affected by the inlet SO 3 concentration, slurry temperature, the inlet flue gas temperature, liquid-to-gas ratio, and spray coverage (Wu et al, 2017b;Zheng et al, 2018). Wu et al (2017a) reported that the removal efficiency of SO 3 can be improved from 30-40% to greater than 60% by using a novel process based on heterogeneous vapor condensation.…”
Section: Analysis Of So3 Control Routesmentioning
confidence: 99%
“…These can, therefore, enter the lungs and endanger human health [6][7][8][9]. Traditional dust removers, such as cyclone dust collectors and electrostatic precipitators (ESPs), although with high efficiency in decreasing the mass concentration of particles, exhibit low efficiency in removing PM 1 (85% or less) [10][11][12]. Wet electrostatic dust removal devices cover a large area, and they increase equipment operating cost.…”
Section: Introductionmentioning
confidence: 99%